From user insights to foresights: Applying video-based ethnographic narratives and user innovation in NPD - Sakellariou, Evy; Karantinou, Kalipso; Goffin, Keith (Elsevier, 2020)
Video-based ethnographic narratives is an advanced ethnographic mode for user innovation and user foresights. This mode adopts both an emic and an etic research perspective that complement each other.User “logos”, “ethos”, “pathos” and “topos” are the antecedents for ordinary user innovation.